PENERAPAN MODEL PEMBELAJARAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) DENGAN MEDIA PADLET UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS BERITA - Nyoman Astawan; Masliana Agustini; Kukuh Andreas (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
The aim of this research is to determine the improvement in the ability to write news texts in Indonesian language lessons with students in class VIII SMP Tunas Bangsa Semester 1 of the 2022/2023 school year after implementing the CIRC (Cooperative Integrated Reading And Composition) learning model with padlet media. This type of research is classroom action research (PTK) with the research subjects being 27 students in class VIII SMP Tunas Bangsa Semester 1. Data on student learning outcomes was collected using a news text writing test. After conducting research, it can be concluded that the application of the CIRC (Cooperative Integrated Reading And Composition) learning method using paldlet media can effectively improve the ability to write news texts. The increase in the ability to write news texts is marked by an increase in students' learning completeness, namely the average score in cycle I was 77.15 and the average score in cycle II was 83.89.